Where Have All the Teachers Gone? - Fetler, Mark (Education Policy Analysis Archives, 1997)
A rising need for teachers is projected for California and the nation during the next decade. Sound policy for teacher preparation should not only foster a capable workforce, it should also assure that the supply of qualified teachers balances with employment demand. A conceptual model is proposed to describe the flow of individuals through teacher preparation programs and the workplace. In California the workforce is projected to grow by thirty percent over the next ten years, stimulating the demand for teachers. At present the number of newly credentialed teachers exceeds the number hired. However, the apparent abundance masks an oversupply of teachers in some curricular and geographic areas and shortages elsewhere. Evidence for a lack of balance between supply and demand is found in an upward trend of emergency hiring of teachers who do not meet all requirements for a credential and low employment rates for first-time college and university prepared teachers. The asymmetry between supply and demand could be redressed partly through better retention of working teachers and closer coordination of preparation programs with the needs of schools in their service areas.